Identification of leukemia stem cells in acute myeloid leukemia and their clinical relevance - Hoang, Thanh Van; Zepeda-Moreno, Abraham; Ho, Anthony Dick (Biotechnology journal, 2012)
Acute myeloid leukemia (AML) is considered to be a disease of stem cells. A rare defective stem cell population is purported to drive tumor growth. Similarly to their normal counterparts, leukemic stem cells (LSC) divide extreme slowly. This may explain the ineffectiveness of conventional chemotherapy in combatting this disease. Novel treatment strategies aimed at disrupting the binding of LSC to stem cell niches within the bone marrow might render the LSC vulnerable to chemotherapy and thus improving treatment outcome. This review focuses on the detection of LSC, our current knowledge about their cellular and molecular biology, and LSC interaction with the niche. Finally, we discuss the clinical relevance of LSC and prospective targeted treatment strategies for patients with AML.